Detection of anaplasma phagocytophilum in Lipoptena fortisetosa deer keds from moose and roe deer in Lithuania - Klepeckienė, Kamilė; Radzijevskaja, Jana; Paulauskas, Algimantas (2018)
Deer keds are a blood-sucking ectoparasites of the family Hippoboscidae. One of the species – Lipoptena fortisetosa were analyzed by a nested DNA polymerase chain reaction (PCR) technique from moose (Alces alces) and roe deer (Capreolus capreolus). L. fortisetosa identification has been done using four primers CI-J-1632, CI-N-2329, CI-J-1718, CI-N-2191. The present study is the first molecular identification of L. fortisetosa in Lithuania. The 16S rRNA sequences of L. fortisetosa in this study were 97 – 99% identical to those in GenBank. L. fortisetosa individuals were examined for gram-negative bacteria Anaplasma phagocytophilum using four primers MAP4AP5, MSP4AP3, msp4f, msp4r. A. Phagocytophilum pathogen was not detected in these specimens. Studies prove that L. Cervi transmit A. Phagocytophilum (Buss et al., 2016, de Bruin et al., 2015). This strong genetic relationship among L. fortisetosa and L. Cervi sequences suggest potential transmission among mammalian hosts by L. fortisetosa too. Although further studies are required to positively confirm L. fortisetosa as a biological vector of A. Phagocytophilum pathogen.